Mental Health of the Participants of the Third Age University Program: A Cross-Sectional Study - Cybulski, Mateusz; Cybulski, Łukasz; Cwalina, Urszula; Kowalczuk, Krystyna; Krajewska-Kułak, Elżbieta (Frontiers in Psychiatry, 2020)
Introduction: Population aging is a progressive demographic phenomenon observed in all countries worldwide. The progressive global process of population aging poses many threats, especially in the context of the mental health of the elderly. Third Age Universities (UTA) are an essential preventive measure shown to improve the quality of life and psychological wellbeing of the elderly. Objectives: The aim of this study was to analyze the mental status of older persons attending UTA in Poland, with particular emphasis on sociodemographic sources of variance in psychological indices. Methods: The study included a group of the UTA program participants from Poland. A total of 247 persons were enrolled, among them 215 women and 32 men. The study was carried out as a diagnostic survey, using the following validated psychometric scales: MDQ, GDS, GHQ-28, AIS, CECS, STAI and SMAST-G. Results: The vast majority of the respondents did not screen positively for possible bipolar disorder. More than 90% of the participants presented with the symptoms of mild depression, and more than one-third had manifestations of non-psychotic mental morbidity. Nearly half of the respondents had complaints associated with insomnia, and in more than one-fourth, SMAST-G score raised suspicion of problem alcohol drinking. Retired participants were shown to present with significantly higher levels of anger control than the occupationally active respondents. Respondents with poor economic status had significantly higher levels of symptoms for non-psychotic mental disorders. Men significantly more often than women showed symptoms raising suspicion of alcohol-related problems. Discussion: In conclusion, the study group was characterized primarily by the mild depressive and anxiety symptoms. The mental health of the Polish participants of the UTA program was significantly modulated by their socio-occupational and marital status, and financial condition. The study showed that persons with likely problem alcohol drinking differed from other respondents in terms of the occurrence of possible bipolar disorder, depression, and non-psychotic symptoms of mental disorders, state and trait anxiety levels and anger control. There is a need for further research in the field of mental health status in the UTA seniors to determine the prevalence of these phenomenon on a national scale.